To expand the expression \(-\frac{7}{6}(3g + 2)\), we distribute \(-\frac{7}{6}\) to both terms inside the parentheses:
\[ -\frac{7}{6} \cdot 3g - \frac{7}{6} \cdot 2 \]
Calculating each term:
-
For the first term: \[ -\frac{7 \cdot 3g}{6} = -\frac{21g}{6} = -\frac{7g}{2} \quad (\text{since } \frac{21}{6} = \frac{7}{2}) \]
-
For the second term: \[ -\frac{7 \cdot 2}{6} = -\frac{14}{6} = -\frac{7}{3} \quad (\text{since } \frac{14}{6} = \frac{7}{3}) \]
Putting it all together, we get:
\[ -\frac{7}{2}g - \frac{7}{3} \]
Thus, the fully expanded expression is:
\[ -\frac{7}{2}g - \frac{7}{3} \]
The correct response from your options is: \[ −\frac{7}{2}g−\frac{7}{3} \]